A systematic review: Teacher job performance - Retamozo Mendoza , Natalia Cristina (2025)
The purpose of this research paper is to conduct a review of documents on job performance from a brief theoretical perspective and analyze the aforementioned concept. Therefore, the article's objective is to explore the epistemological concept and definitions of teacher job performance by different authors. It will describe the actions and behaviors carried out by teachers over time, laying the foundations for the concept of job performance that helps achieve the objectives proposed by educational institutions. It will also specify the method of teacher performance evaluation and its limitations.